PENGARUH KUALITAS PELAYANAN DAN CITRA MEREK TERHADAP KEPUASAN NASABAH PADA ASURANSI JIWA SINARMAS DI JAKARTA - Felicia Tjusila; Dede Solihin (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect of Service Quality and Brand Image on Customer Satisfaction at Sinarmas Life Insurance in Jakarta. The method used is the Quantitative Associative method. The population in this study were Customers at Sinarmas Life Insurance in Jakarta with a sample size of 100 respondents. The data analysis method used simple linear regression test, multiple linear regression, correlation coefficient, determination coefficient, partial t test and F test. The results of this study indicate that service quality has a positive and significant effect on customer satisfaction at Sinarmas Life Insurance in Jakarta, this can be seen from the simple linear regression equation Y = 0.367 + 0.575X1. The correlation value is 0.854 (very strong). The determination coefficient value is 72.9% and the tcount value is 16.245> ttable 1.984 or the Sig value is 0.000 <0.05, then H1 is rejected and H1 is accepted, meaning that there is a partial effect of service quality on customer satisfaction at Sinarmas Life Insurance in Jakarta. Brand Image has a positive and significant effect on customer satisfaction at Sinarmas Life Insurance in Jakarta, this can be seen from the simple linear regression equation Y = 3.491 + 0.592X2. The correlation value is 0.768 (strong). The determination coefficient value is 59.1% and the t-value is 11.888> t-table 1.984 or the Sig value is 0.000 <0.05, so H2 is rejected and H2 is accepted, meaning that there is a partial influence of brand image on customer satisfaction at Sinarmas Life Insurance in Jakarta. Simultaneously, Service Quality and Brand Image have a positive and significant effect on customer satisfaction at Sinarmas Life Insurance in Jakarta, this can be seen from the results of the multiple linear regression test Y = -0.753 + 0.434X1 + 0.210X2, the correlation value is 0.871 (very strong). The determination coefficient value is 75.9% and the F count value is 153.078 > F table 3.93 or the Sig value is 0.000 < 0.05, so Ho3 is rejected and Ha3 is accepted, meaning that there is a simultaneous influence of service quality and brand image on customer satisfaction at Sinarmas Life Insurance in Jakarta.